2013
DOI: 10.1002/anie.201308063
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a G‐quadruplex Bound to the Bisquinolinium Compound Phen‐DC3

Abstract: Phen-DC3 is a highly promising compound that specifically targets G-quadruplexes, with potent biological effects observed in vivo. We used NMR spectroscopy to solve the structure of the complex formed between Phen-DC3 and an intramolecular G-quadruplex derived from the c-myc promoter. Structural information revealed that Phen-DC3 interacts with the quadruplex through extensive π-stacking with guanine bases of the top G-tetrad. On the basis of our structure, modifications are proposed for the development of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
179
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(190 citation statements)
references
References 50 publications
6
179
1
Order By: Relevance
“…68 As a result, ligands were 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the G-quartet ( Figure S13, Supporting Information). In addition, both ligands in the presence of telomeric antiparallel G-quadruplex DNA underwent energetically unfavorable amide bond rotations during the course of MD simulations ( Figure S12, Supporting Information).…”
Section: 74mentioning
confidence: 93%
See 1 more Smart Citation
“…68 As a result, ligands were 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the G-quartet ( Figure S13, Supporting Information). In addition, both ligands in the presence of telomeric antiparallel G-quadruplex DNA underwent energetically unfavorable amide bond rotations during the course of MD simulations ( Figure S12, Supporting Information).…”
Section: 74mentioning
confidence: 93%
“…Imino-protons in the 1 H NMR spectra of quadruplex and quadruplex-ligand complex provide valuable insights into stoichiometry and binding mode of ligands. It is reported that when ligands bind to quadruplex by end-stacking mode, the imino-proton peaks of all G-quartets get shielded, which leads to up-field chemical shifts [66][67][68]. In contrast, when ligands bind to grooves of quadruplex, chemical shifts of imino protons are unaffected or undergo only nominal changes 39,65,69.…”
mentioning
confidence: 90%
“…S1); these ligands are known for their high affinity for G-quartets, most likely due to strong p-p stacking interactions (25)(26)(27)(28). The analysis of calorimetric (DSC and ITC) and spectroscopic (CD and FL) data obtained in solutions with K þ (see Fig.…”
Section: Thermodynamic Analysis Of Binding-induced Structural Transitmentioning
confidence: 99%
“…Further research is required to dissect how this circumstantial evidence actually relates to the regulation of genes by G-quadruplexes. Other compounds that have been studied for their interaction with the promoter G-quadruplex of MYC include quindolines [106][107][108], actinomycin D [109] and Phen-DC (3) [110]. In addition, platinum complexes [111] and the synthetic telomestatin derivative S2T1-6OTD [112] also show significant selectivity for G-quadruplex DNA and destabilize the MYC promoter G-quadruplex, leading to downregulation of expression.…”
Section: Gene Transcription and Translationmentioning
confidence: 98%